A Smartphone Game to Prevent HIV Among Young Africans (Tumaini): Assessing Intervention and Study Acceptability Among Adolescents and Their Parents in a Randomized Controlled Trial - Sabben, Gaëlle; Mudhune, Victor; Ondeng'e, Ken; Odero, Isdorah; Ndivo, Richard; Akelo, Victor; Winskell, Kate (JMIR Publications, 2019)
BackgroundYoung people aged 15 to 24 years account for one-third of new adult HIV infections. Controlling the HIV epidemic requires effective interventions targeted toward young people and their needs. Smartphone games offer a promising avenue for reaching this population with evidence-based HIV prevention interventions. It is crucial to the effectiveness of these interventions that they be acceptable and intrinsically motivating to adolescents as well as acceptable to their parents. ObjectiveTumaini is a narrative-based smartphone game designed to help prevent HIV among young Africans aged 11 to 14 years by delaying first sex and increasing condom use at first sex. Following a 16-day feasibility study of Tumaini, we assessed the acceptability (1) of the intervention, where acceptability was operationalized as appeal, relevance, value, usability, and understandability, and (2) of this study and a planned future randomized controlled efficacy trial. MethodsDuring the randomized feasibility study (n=60) of Tumaini in western Kenya in spring 2017, 30 participants used the intervention on a study-provided smartphone. The app automatically logged participant interaction with the game in time-stamped log files. All 30 participants completed an Audio Computer-Assisted Self-Interview-based game experience survey, and 27 took part in 4 focus group discussions (FGDs) about the game's appeal, relevance, value, usability, and understandability. Their parents (n=22) also participated in 4 FGDs about the acceptability of the intervention, of this study, and of a planned efficacy trial. Survey data were analyzed using SAS software (SAS Institute Inc); FGD transcripts were coded and analyzed in MAXQDA 12 (Verbi GmbH); and gameplay log files were analyzed using Microsoft Excel. ResultsAdolescent participants' survey responses indicated that Tumaini scored well with players on all indicators of acceptability (appeal, relevance, value, usability, and understandability). Focus group analyses aligned with these findings and emphasized a high degree of player engagement with the game, which was supported by log file analysis. Adolescent participants were eager for additional content, and parents were receptive to a longer study involving biomarkers, based on their positive experiences with this study. There is scope to improve communication with parents about their role in the intervention. As the game was tested in beta version, there is also scope to fine-tune some of the game mechanics to increase usability. ConclusionsThis study shows the strong acceptability of an interactive smartphone-based game both to adolescents and their parents in western Kenya and that of the study methods used to pilot-test the intervention. It also suggests that longitudinal efficacy studies of this type of intervention, including those using biomarkers, have the potential to be acceptable among parents. Trial RegistrationClinicalTrials.gov NCT03054051; https://clinicaltrials.gov/ct2/show/NCT03054051 (Archived by WebCite at http://www.webcitation.org/70U2gCNtW)